Pneumatosis Intestinalis: Not Always a Surgical Indication. (12th November 2012) - Zhang, Haijing; Jun, Stephanie L.; Brennan, Todd V.
Abstract : We present a case of pneumatosis intestinalis (PI) of the colon in the setting of inflammatory bowel disease that was treated with medical management rather than emergent surgery. While the reflex response to extraluminal air in the abdomen is abdominal exploration, consideration of the clinical context in which PI is discovered and an understanding of a complete differential diagnosis of the sources of PI is critical to avoiding unnecessary surgery.